PELATIHAN PEMBELAJARAN MENDALAM (DEEP LEARNING) UNTUK PENINGKATAN KOMPETENSI PEDAGOGIK GURU MADRASAH IBTIDAIYAH - Machfud, Nailul Ulah Al Chumairoh; Dwi Astutiek; Agus Setyawanto; Asyhari Zubair; Agung Riandra; Aditiya Permana Putra Setiawan (AlMurtado Journal of Social Innovation and Community Service, 2025)
The transformation of 21st-century education requires teachers to create student-centered learning, integrate technology, and foster higher-order thinking skills. This community service project aims to enhance the pedagogical competence of teachers at MIS Tarbiyatul Islamiyah through a workshop on implementing the deep learning curriculum. The implementation involved needs assessment, training module development, interactive workshops, and mentoring on designing deep learning–based lesson plans. The results indicate an 82% increase in teachers’ understanding of the deep learning curriculum and improved ability to design reflective, collaborative, and authentic learning experiences. This program also fostered a professional learning culture within the madrasa and serves as a model for implementing innovative curricula in Islamic primary education institutions.